A database of [(11)C]WAY-100635 binding to 5-HT(1A) receptors in normal male volunteers: normative data and relationship to methodological, demographic, physiological, and behavioral variables. - Rabiner, E; Messa, C; Sargent, P; Husted-Kjaer, K; Montgomery, A; Lawrence, A; Bench, C; Gunn, R; Cowen, P; Grasby, P (2002)
PET studies of [(11)C]WAY-100635 binding are proving to be a useful tool to evaluate 5-HT(1A) receptor function in vivo in humans. We describe the pattern of [(11)C]WAY-100635 binding in 61 healthy male brains and examine its variability. For all PET scans, binding potential (BP) values for [(11)C]WAY-100635 in different regions were calculated using a simplified reference tissue model, with the cerebellum as reference region. Specifically we describe (1) region of interest and SPM databases of PET [(11)C]WAY-100635 binding, including test-retest variability; (2) the sensitivity of [(11)C]WAY-100635 binding to manipulations of endogenous 5-HT; and (3) correlations between [(11)C]WAY-100635 binding and radiochemical, demographic, physiological, and behavioral variables. The regional distribution of [(11)C]WAY-100635 binding in healthy human brain was similar to that reported in vitro. The test-retest variability was approximately 12% (range 9-16%) and was similar for all methods of regional sampling. The binding of [(11)C]WAY-100635 was insensitive to changes in brain 5-HT induced by tryptophan infusion and depletion. Although BP values varied greatly across subjects (range 2.9-6.8), there were no significant correlations of regional and global BP with common radiochemical, demographic, physiological, and personality variables. Specifically, in contrast with two recent small studies, we found no decline of [(11)C]WAY-100635 binding with age in our large cohort over the age range of 24 to 53 years. Assessment of 5-HT(1A) receptors in vivo using PET and [(11)C]WAY-100635 gives reliable measures of 5-HT(1A) binding. The large between-subject variability observed could not be explained by common methodological, physiological, or behavioral factors and hence the biological basis of this variability remains to be clarified.